Palmitoylethanolamide Reduces Neuropsychiatric Behaviors by Restoring Cortical Electrophysiological Activity in a Mouse Model of Mild Traumatic Brain Injury - Guida, Francesca; Boccella, Serena; Iannotta, Monica; De Gregorio, Danilo; Giordano, Catia; Belardo, Carmela; Romano, Rosaria; Palazzo, Enza; Scafuro, Maria A.; Serra, Nicola; de Novellis, Vito; Rossi, Francesco; et al. (Frontiers in Pharmacology, 2017)
Traumatic brain injury (TBI) represents a major public health problem, which is associated with neurological dysfunction. In severe or moderate cases of TBI, in addition to its high mortality rate, subjects may encounter diverse behavioural dysfunctions. Previous reports suggest that an association between TBI and chronic pain syndromes tends to be more common in patients with mild forms of brain injury. Despite causing minimal brain damage, mild TBI (mTBI) often leads to persistent psychologically debilitating symptoms, which can include anxiety, various forms of memory and learning deficits, and depression. At present, no effective treatment options are available for these symptoms, and little is known about the complex cellular activity affecting neuronal activity that occurs in response to TBI during its late phase. Here, we used a mouse model to investigate the effect of Palmitoylethanolamide (PEA) on both the sensorial and neuropsychiatric dysfunctions associated with mTBI through behavioural, electrophysiological, and biomolecular approaches. Fourteen-day mTBI mice developed anxious, aggressive, and reckless behaviour, whilst depressive-like behaviour and impaired social interactions were observed from the 60th day onwards. Altered behaviour was associated with changes in interleukin 1 beta (IL-1β) expression levels and neuronal firing activity in the medial prefrontal cortex (m-PFC). Compared with vehicle, PEA restored the behavioural phenotype and partially normalised the biochemical and functional changes occurring at the supraspinal level. In conclusion, our findings reveal some of the supraspinal modifications responsible for the behavioural alterations associated with mTBI and suggest PEA as a pharmacological tool to ameliorate neurological dysfunction induced by the trauma.